Main Areas Of Improvement Operational-Search Activities In The Customs Authorities - Ilyin Vyacheslav Mikhailovich (Genius Journals, 2024)
The article is devoted to the role of operational-investigative activities in the customs authorities in identifying and suppressing crimes in the field of customs activities, as well as issues of the effective waysof its organization.
Keywords: Operational-investigative activity; customs crimes